Talking about intimate partner violence in multi-cultural antenatal care: a qualitative study of pregnant women's advice for better communication in South-East Norway - Lisa Maria Garnweidner-Holme; Mirjam Lukasse; Miriam Solheim; Lena Henriksen (BMC, 2017)
Abstract Background Intimate partner violence (IPV) against women constitutes a major public health problem. Antenatal care is considered a window of opportunity to disclose and to communicate about IPV. However, little is known about how women from different ethnic backgrounds wish to communicate about their experiences with IPV during pregnancy in antenatal care. The aim of the present study was to explore how women from different ethnic backgrounds experienced IPV and what their recommendations were about how midwives should communicate about IPV in antenatal care. Methods Qualitative individual interviews with eight women who had experienced IPV during pregnancy were conducted and analysed using thematic analysis. The participants were purposively recruited from three crisis shelters in South-East Norway. Results The participants either had immigrant backgrounds (n = 5) or were ethnic Norwegians (n = 3). All participants received antenatal care by a midwife. Although none of the participants were asked about IPV during antenatal care, they wished to talk about their experiences. Most participants felt that it would be important for the midwife to make them aware that they were victims of violence. Participants offered different suggestions on how and when midwives should talk about IPV. Facilitators to talk about IPV with the midwife were a good relationship with and the trustworthiness of the midwife, information about possible negative health outcomes for the newborn owing to IPV and knowing that the midwife could help them. The main barriers to talk about IPV with the midwife were that the participants were accompanied by their husbands during antenatal care, fear that the Child Welfare Service would take away their children after disclosure and cultural acceptance of violence. Participants with immigrant backgrounds also experienced difficulties in talking about IPV owing to their limited language skills. They thought that professionally trained interpreters with experience of IPV could overcome this barrier. Conclusion Even though none of the participants were asked about IPV in antenatal care, they offered different suggestions on how and when midwives should talk about IPV. Participants irrespective of their ethnical backgrounds perceived antenatal care as a key area to facilitate disclosure of IPV. Midwives' communication and strategic skills to address IPV are crucial for help-seeking women. Training midwives' skills in culture-sensitive communication might help to overcome cultural barriers to talk about violence.